The Effect of Usefulness and Convenience on Members’ Interest in Using Mobile UGT at BMT UGT Nusantara, Pesanggaran Branch - Nurdiana, Alfina; Zamroji, Yunus (Dinasti International Journal of Economics, Finance & Accounting, 2025)
his study aims to analyze the effect of ease and usability on member interest in using Mobile UGT at BMT UGT Nusantara Pesanggaran Branch . The background of this study is based on the increasing development of information technology that encourages microfinance institutions, such as BMT, to adopt mobile- based applications as a means of service to their members. The object of this study is members of BMT UGT Nusantara Pesanggaran Branch who use the Mobile UGT service. This study uses a quantitative approach with a survey method and data analysis techniques using multiple linear regression. Data were collected by distributing questionnaires to selected respondents with samples taken by purposive sampling from 40 respondents who have used the UGT mobile application . The results of the study indicate that ease and usefulness have a significant positive influence on members' interest in using Mobile UGT. Ease of use of the application and perceived usefulness by members are the main factors that increase their interest in continuing to use the mobile service . This finding contributes to the development of information systems in BMT to improve the quality of service to members.